Clinical outcomes after more conservative management of patent ductus arteriosus in preterm infants - Cristina Borràs‐Novell; Ana Riverola; Victoria Aldecoa‐Bilbao; Montserrat Izquierdo; Monica Domingo; Martín Iriondo (Brazilian Society of Pediatrics, 2020)
Objective: Management of patent ductus arteriosus is still controversial. This study aimed to describe the impact of a more conservative approach on treatment rates and on main outcomes of prematurity, especially in preterm infants with <26 weeks of gestation. Method: Clinical charts review of infants ≤30 weeks with patent ductus arteriosus between 2009 and 2016 at two centers. In 2011, the authors changed patent ductus arteriosus management: in first period (2009-2011), patients who failed medical treatment underwent surgical closure; in second period (2012-2016), only those with cardiopulmonary compromise underwent surgical ligation. Medical treatment, surgical closure, mortality, and survival‐without‐morbidity were compared. Results: This study included 188 patients (27 ± 2 weeks, 973 ± 272 grams); 63 in P1 and 125 in P2. In P2, significantly lower rates of medical treatment (85.7% P1 versus 56% P2, p < 0.001) and surgical closure (34.5% P1 versus 16.1% P2, p < 0.001) were observed. No differences were found in chronic lung disease (28.8% versus 13.9%, p = 0.056), severe retinopathy of prematurity (7.5% versus 11.8%, p = 0.403), necrotizing enterocolitis (15.5% versus 6.9%, p = 0.071), severe intraventricular hemorrhage (25.4% versus 18.4%, p = 0.264), mortality (17.5% versus 15.2%, p = 0.690) or survival‐without‐morbidity adjusted OR = 1.10 (95% CI: 0.55-2.22); p = 0.783. In P2, 24.5% patients were discharged with patent ductus arteriosus. The subgroup born between 23 and 26 weeks (n = 82) showed significant differences: lower incidence of chronic lung disease (50% versus 19.6%, p = 0.019) and more survival‐without‐morbidity (20% versus 45.6%, p = 0.028) were found. Conclusion: A conservative approach in preterm infants with patent ductus arteriosus can avoid medical and surgical treatments, without a significant impact in survival‐without‐morbidity. However, two‐thirds of preterm infants under 26 weeks are still treated. Resumo: Objetivo: O tratamento da persistência do canal arterial ainda é controverso. Nosso objetivo foi descrever o impacto de uma abordagem mais conservadora em nossas taxas de tratamento e nos principais desfechos da prematuridade, especialmente em prematuros com < 26 semanas de gestação. Método: Revisão de prontuários de lactentes com ≤ 30 semanas e persistência do canal arterial entre 2009‐2016 em dois centros. Em 2011, mudamos o manejo da persistência do canal arterial: no primeiro período (2009‐2011), os pacientes que não apresentaram sucesso com o tratamento clínico foram submetidos a fechamento cirúrgico; no segundo período (2012‐2016), apenas aqueles com comprometimento cardiopulmonar foram submetidos ao fechamento cirúrgico. Comparamos o tratamento clínico, fechamento cirúrgico, mortalidade e sobrevida sem morbidade. Resultados: Foram incluídos 188 pacientes (27 ± 2 semanas, 973 ± 272 gramas); 63 em P1 e 125 em P2. Em P2, foram observadas taxas significativamente mais baixas de tratamento clínico (85,7% no P1 versus 56% no P2, p < 0,001) e fechamento cirúrgico (34,5% no P1 versus 16,1% no P2, p < 0,001). Não foram encontradas diferenças em relação à doença pulmonar crônica (28,8% versus 13,9%, p = 0,056), retinopatia grave da prematuridade (7,5% versus 11,8%, p = 0,403), enterocolite necrosante (15,5% versus 6,9%, p = 0,071), hemorragia intraventricular grave (25,4% versus 18,4%, p = 0,264), mortalidade (17,5% versus 15,2%, p = 0,690) ou OR ajustado pela sobrevida sem morbidade = 1,10 (IC95%: 0,55‐2,22); p = 0,783. Em P2, 24,5% dos pacientes receberam alta com persistência do canal arterial. O subgrupo nascido entre 23 a 26 semanas (n = 82) apresentou diferenças significativas, foram encontradas menor incidência de doença pulmonar crônica (50% versus 19,6%, p = 0,019) e maior sobrevida sem morbidade (20% versus 45,6%, p = 0,028). Conclusão: Uma abordagem conservadora em prematuros com persistência do canal arterial pode evitar tratamentos clínicos e cirúrgicos, sem um impacto significativo na sobrevida sem morbidade. No entanto, dois terços dos prematuros com menos de 26 semanas ainda são tratados. Keywords: Patent ductus arteriosus, Ductal patency, Preterm infant, Ibuprofen, Surgical ligation, Surgical closure, Palavras‐chave: Persistência do canal arterial, Patência do canal, Prematuro, Ibuprofeno, Ligadura cirúrgica, Fechamento cirúrgico